Derivatives and Corporate Hedging: Participation and Volume Decisions in the Life insurance Industry - wen, wei (2006)
Abstract This paper examines the determinants of the use of financial derivatives in the United Kingdom life insurance industry. Using data from the statutory returns of a total sample (N=2346) for the years 1995 to 2005, three separate models were estimated for probability and extent of use of financial derivatives by life insurers for the purpose of hedging risks a Probit model, a Tobit regression model and a Heckman selection model. Our results indicate that the propensity to use derivatives is positively and highly significantly related with a firms size, which supports the informational economies and economies of scale hypothesis. Derivatives participation decision is also found to be significantly and positive related with organizational form and group status. To test the relationship between the firm leverage and derivatives usage, we add two control variables whether the insurers are linked or non-linked insurance companies as well as the equity investments by the firms. Although we did not find any relationship between leverage and derivatives use, as a result, the highly significantly positive relationship between non-linked insurers and derivatives usage and the significant relationship between the derivatives participation decisions and the firms investments on equity support the hypothesis that life insurers use derivatives to hedge risks rather than as a speculation means of income generation. Finally, we find that life insurers are more likely to hedge in a greater extent when they are non-linked business and have a larger firm size.